Growth performance and feed utilization of juvenile marble goby (oxyeleotris marmorata) fed acidified diets - Teoh, Chui Fen; Lim, Leong Seng; Gunzo Kawamura; Annita Seok Kian Yong; Rossita Shapawi (Penerbit UMS, 2019)
The present study was aimed at evaluating the growth performance and feed utilization of marble goby (Oxyeleotris marmorata) juveniles fed with the acidified diets (AD). In feeding trial I, five fish meal-based diets were prepared [control (pH 6.0), AD 5.3, 4.3, 3.2 and 2.5]. Each diet was fed to triplicate batches of wild-caught O. marmorata (19 fish/ tank; total length, TL = 4.72±0.46 cm) for 8 weeks. The control, AD 5.3, and AD 4.3 treatments were terminated at week 4, due to drastic decline in total feed intake (TFI=0–0.05 g) and weight loss (weight gain, WG = -15.3 to -16.9%) in the fish. The AD 3.2 and AD 2.5 treatments were continued until week 8. Fish fed with the AD 3.2 showed significantly higher (P < 0.05) TFI (0.98 g) compared to those fed with the AD 2.5 (0.73 g) at the end of the trial. Feeding trial II was done to assess the long-term effects of AD for another 7 weeks. Thirty fish specimens were randomly selected from each of AD 3.2 and AD 2.5 treatments and stocked individually in 7 L aquaria to eliminate the territorial behaviour that was observed in the first trial. At the end of the experiment, fish fed AD 3.2 attained significantly higher (P < 0.05) WG (34%) than those fed AD 2.5 (13%). However, the growth performance and feed utilization results of the present study were very poor compared to those fed the normal fishmeal-based diet as is evident from synthesis of data from the literature review. Feeding of acidified diets was, therefore, not recommended for an extended period (> 3 weeks). Nevertheless, based on the strong preference of the fish for AD, it is worth trying to develop a weaning protocol using these diets as the starter feed and then slowly replacing them with the normal diet.